Animal Names for Hebrew Bible Female Prophets - Scheuer, Blazenka (2017)
This article explores the literary and ideological dimensions of zoomorphic names for Deborah (bee) and Huldah (weasel) - two of the Hebrew Bible female prophets. The two women stand out among the female protagonists of the Hebrew Bible in three ways: they are the only female prophets endowed with textual legacy, they are remarkably successful in roles usually reserved for men, and they are the only women named after unclean animals. In this article, I argue that biblical authors use animal names to enhance the characterisation of the two women and to foreshadow the outcome of their narratives. Perceived as a bee, Deborah emerges as a triumphant weapon of war launched against the enemies of her people. Perceived as a weasel, Huldah appears as masterful in finding ways to solve intricate situations. At the same time, the use of names of unclean animals works to undermine the achievements and capacity of the two women, thereby consolidating the divide between male and female roles. Zoomorphic names of unclean animals suggest that although imaginable, and sometimes indispensable, female leadership is essentially extraordinary and must be viewed with suspicion.